E-Business : At A Glance Indonesia Online Shop Agent - Arnes Yuli Vandika; Samsul Arifin; Eka Imama Novita Sari; Debi Herlina Meilani (UBL, 2013)
Condition of the seller and buyer are more numerous and scattered in Indonesia is quite difficult to communicate and conduct buying and selling process. Natural conditions that many Indonesian island is also one of its own difficulties. It has been strived for by the experts to make the mechanism of electronic business systems that can communicate between sellers and buyers. In the developed countries as an example of the American, British and French systems to work optimally, it means the system is very little human contact with the end-user. The system can be set to work as an intermediary that can automatically contact the seller or buyer. online shop agent in Indonesia for example, can be an effective solution to improve the economy indirectly to our government. And so is the main element of our own society.